Hubungan Problem Focused Coping dan Dukungan Sosial terhadap Stres Mengerjakan Skripsi pada Mahasiswa di Universitas Muhammadiyah Sidoarjo - Saladin, Sultan; Nastiti, Dwi (Institut Agama Islam Nasional Laa Roiba Bogor, 2026)
This research is motivated by the phenomenon of stress experienced by final semester students at Universitas Muhammadiyah Sidoarjo (UMSIDA) who have low emotional well-being, decreased cognitive behavior and weakened physical conditions. The purpose of this study is to determine the effect of problem focused coping and social support on thesis-related stress. The research method used is quantitative correlation with a population of 3,734 final semester students at UMSIDA. The sample size is 320 students based on the Isaac & Michael table with a 5% margin of error. The sample was determined using purposive sampling technique. The variables in this study were problem focused coping, social support, and thesis writing stress. Data collection in this study used three psychological scales based on the Likert scale model adopted from previous studies. The hypothesis in this study was that there is a relationship between problem focused coping and social support on thesis writing stress. Data analysis in this study used mulitple correlations statistical test with the help of SPSS 26.0 for Windows.